Intervention of Astragalus Membranaceus Extract in rats of spinal cord injury: a systematic review and meta-analysis - Wu, Hongli; Yu, Lanlan; Yang, Hao; Li, Jiahao; Deng, Jing; Zhou, Zichao; Tao, Yufeng; Chen, Fengjiao; Zhang, Leyi; Zhang, Chi (Frontiers in Neurology, 2025)
ObjectiveSpinal cord injury (SCI) causes motor, sensory and autonomic dysfunction below the level of injury and its incidence is increasing every year. Astragalus Membranaceus Extract (AME) has received attention in spinal cord injury in recent years, but its specific effects in spinal cord injury are unclear.MethodsDatabases of PubMed, Embase, WOS, Cochrane Library, FMRS, Clinical trial, CNKI, VIP, and WangFang were searched from their establishment to December 1, 2024 using the following terms: “Astragalus propinquus,” “Huang qi,” “Astragalus mongholicus Bunge,” “Spinal cord injuries,” “spinal cord diseases,” “spinal cord trauma.” To ensure comprehensiveness, the search strategy included both traditional names (Astragalus) and scientific names (Astragalus membranaceus). Only studies published in Chinese or English were included. Cross-sectional studies, survey designs, quality improvement studies, and other study designs that did not meet the inclusion criteria were excluded.ResultsAfter screening, a total of 16 studies with 996 animals were included in the review. Astragalus Membranaceus Extract (AME) administration was associated with more significant functional recovery (mean difference [MD] = 3.68, 95% CI = 2.74, 4.62). Subgroup analyses showed the best functional recovery of the spinal cord when the dose exceeded 20 units and the duration of treatment was less than 14 days.ConclusionOur study suggests that AME has therapeutic potential for spinal cord injured rats. Further studies are needed to determine if this can be developed into a new alternative therapy through experimental and clinical studies with larger samples.Systematic review registrationIdentifier: CRD42024623721, website: https://www.crd.york.ac.uk/PROSPERO/